A Mosque at Khor Rori. New Evidence for the Islamic Period in Coastal Dhofar - Pavan, Alexia (Archeologie tra Oriente e Occidente, 2026)
Along the southern coast of Oman, the ancient, fortified town of Sumhuram stands in a landscape rich in archaeological remains. Between 1996 and 2019, the Italian Mission to Oman (IMTO, University of Pisa) carried out extensive investigations at the site and in its surrounding territory. With the aim of reconstructing settlement patterns across different periods, the research examined several structures, including a mosque located on the bank of the lagoon formed by wadi Darbat. Although its precise dating remains uncertain, the mosque represents a small yet meaningful addition to the corpus of Islamic-period evidence from coastal Dhofar. This paper presents the mosque’s architectural features and associated finds and discusses possible interpretations of its isolated location.